Methylation of the PTPRO gene in human hepatocellular carcinoma and identification of VCP as its substrate - Hsu, Shu-hao; Motiwala, Tasneem; Roy, Satavisha; Claus, Rainer; Mustafa, Mufaddal; Plass, Christoph; Freitas, Michael A.; Ghoshal, Kalpana; Jacob, Samson T. (Journal of cellular biochemistry, 2013)
We have previously reported that the gene encoding protein tyrosine phosphatase receptor type-O (PTPRO) is suppressed by promoter methylation in a rat model of hepatocellular carcinoma (HCC) and it functions as tumor suppressor in leukemia and lung cancer. Here, we explored the methylation and expression of PTPRO as well as its function in human HCC. MassARRAY analysis of primary human HCC and matching liver samples (n = 24) revealed significantly higher (P = 0.004) methylation density at the promoter CGI in tumors. Combined bisulfite restriction analysis (COBRA) of another set of human HCC samples (n = 17) demonstrated that the CGI was methylated in 29% of tumors where expression of PTPRO was lower than that in corresponding matching livers. A substrate-trapping mutant of PTPRO that stabilizes the bound substrates was used to identify its novel substrate(s). VCP/p97 was found to be a PTPRO substrate by mass spectrometry of the peptides pulled down by the substrate-trapping mutant of PTPRO. Tyrosyl dephosphorylation of VCP following ectopic expression of wild-type PTPRO in H293T and HepG2 cells confirmed that it is a bona fide substrate of PTPRO. Treatment of PTPRO overexpressing HepG2 cells with Doxorubicin, a DNA damaging drug commonly used in therapy of primary HCC, sensitized these cells to this potent anticancer drug that correlated with dephosphorylation of VCP. Taken together, these results demonstrate methylation and downregulation of PTPRO in a subset of primary human HCC and establish VCP as a novel functionally important substrate of this tyrosine phosphatase that could be a potential molecular target for HCC therapy. J. Cell. Biochem. 114: 1810-1818, 2013. © 2013 Wiley Periodicals, Inc.